1999
DOI: 10.1007/bf02349393
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of wheat, rye, and potatoes by foliar application of134Cs

Abstract: The aim of the study reported in this paper was to derive factors describing the translocation of radiocesium from the green plant parts to the crop. Wheat, rye and potatoes were contaminated and harvested at different growth stages to allow the assessment of the contamination of the crop with known date of the radioactive deposition. At harvest, the cesium concentrations in the crop, the green plant parts (i.e., straw without ears) and the roots were measured. The results show that the contamination of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
2
1
0
2
Order By: Relevance
“…In the same way, 63 Ni translocation from leaves to radish roots decreased with chronic contamination (19 ± 2%), as compared with a single early contamination (36 ± 4%, respectively). This is consistent with the results of Anguissola Scotti (1995) and Gerdung et al (1999), who demonstrated that the translocation of radionuclide 134 Cs from leaves to fruit or to storage organs was reduced by half after fruit or storage organ filling. Another probable explanation is that the interval between the final supply, during chronic contamination, and the harvest was too short to allow the translocation of radionuclides from leaves to fruit or to storage organs (Aarkrog, 1969).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the same way, 63 Ni translocation from leaves to radish roots decreased with chronic contamination (19 ± 2%), as compared with a single early contamination (36 ± 4%, respectively). This is consistent with the results of Anguissola Scotti (1995) and Gerdung et al (1999), who demonstrated that the translocation of radionuclide 134 Cs from leaves to fruit or to storage organs was reduced by half after fruit or storage organ filling. Another probable explanation is that the interval between the final supply, during chronic contamination, and the harvest was too short to allow the translocation of radionuclides from leaves to fruit or to storage organs (Aarkrog, 1969).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance with the works of Baldini et al (1987) and Monte et al (1990) on 137 Cs and 103 Ru, Bengtsson (1992) and Zehnder et al (1995) on 134 Cs and 85 Sr, and Gouthu et al (1999) on Rb, Zn, Fe, Nb, Cr, and Sc, who demonstrated that mobile radionuclides (Cs, Zn, Fe, and Rb) accumulated mainly in the fruit of trees after foliar contamination (in average 25% of the intercepted radioactivity), while radionuclides with a low mobility (Nb, Cr, Sc, Sr) were not present in the fruit. In the same way, Bittel and Clément (1965), Gerdung et al (1999), and Middleton and Squire (1963) showed a translocation of mobile 134 Cs from potato leaves to tubers (storage organ) similar to the 63 Ni translocation observed in our experiment from radish leaves to filling storage roots (20–50% in the potato tubers and 19 ± 2% to 36 ± 4% in the radish roots). These authors also measured a translocation of 134 Cs of 20% from bean leaves to bean fruit, while we found from 24 ± 13% to 48 ± 15% of the retained 63 Ni in the bean fruit (husks and seeds) according to the method of leaf contamination.…”
Section: Discussionsupporting
confidence: 87%
“…Translocation factor geometric mean (%) Aarkrog (1969Aarkrog ( , 1972Aarkrog ( , 1975Aarkrog ( , 1983, Gerdung et al (1999), Middleton (1958Middleton ( , 1959, Shaw et al (1992), Voigt et al (1991). Fig.…”
Section: Elementmentioning
confidence: 97%
“…Також відомо, що зі всієї кількості радіоцезію (у даному випадку 137 Cs), який випав на листову поверхню рослин під час вегетації картоплі, до бульб протягом одного місяця може перейти понад 40 % [14]. Рівень забруднення бульб картоплі майбутнього врожаю також значною мірою залежить від фази росту і розвитку рослини на час випадіння радіоактивного 134 Cs [9]. Картопля, як правило, характеризується відносно низькими значеннями коефіцієнтів переходу радіоцезію, порівняно з іншими продовольчими культурами [16].…”
unclassified
“…Відомості про те, як залежить рівень забруднення сільськогосподарських культур від фенологічної фази їхнього росту і розвитку на час випадіння радіонуклідів, будуть корисними для прогнозування можливого використання врожаю даної культури як продукту харчування. На сьогодні відомі лише окремі публікації з експериментальними даними [9,15,17], що показують, яким чином рівні забруднення надземної маси рослин і бульб картоплі радіоцезієм залежать від того, в якій фазі росту й розвитку радіонуклід надходить на поверхню рослин. У ході експерименту, проведеного протягом трьох років у польових умовах, було досліджено, яким чином 134 Cs, нанесений на листову поверхню рослин картоплі шляхом обприскування вегетуючих рослин у різні фази росту й розвитку водним розчином радіонукліда («мокре» випадіння), переходить із листя у бульби картоплі.…”
unclassified